FAKTOR YANG BERHUBUNGAN DENGAN PELAPORAN INSIDEN KESELAMATAN PASIEN OLEH PERAWAT DI RSUD PANEMBAHAN SENOPATI BANTUL YOGYAKARTA - Astari Ekaningtyas; Nasiatul Aisyah Salim (Jurnal Surya Muda, 2023)
Establishing a patient safety culture is associated with reducing the occurrence of adverse events. One important component of safety culture is the frequency of reporting patient safety incidents. Nurses are reliable information reporters for assessing patient safety outcomes including adverse events. However, nurses have obstacles in reporting patient safety incidents. This study aims to determine the factors associated with the reporting of patient safety incidents by nurses at Panembahan Senopati Hospital, Bantul. The research method is quantitative observational with cross sectional design. A sample of 189 nurses was taken using proportionate stratified random sampling. Data collection using a questionnaire. Data analysis usingspearman rank and logistic regression. The results of the analysis with incident reporting obtained the value of open communication (p value <0,001); expectations & promotion of patient safety by superiors (p value 0,015); feedback about errors (p value 0,007); non punitive response to mistakes (p value <0,001) and management support (p value 0,084). So that the factors related to the frequency of reporting patient safety incidents at Panembahan Senopati Hospital, Bantul are non punitive responses to errors, ope communication, feedback about errors and expectations & promotion of patient safety by superiors. So that hospitals can improve the culture of reporting patient safety incidents by paying attention to the factors that influence itu.